2007
DOI: 10.1002/anie.200603995
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton Fabrication

Abstract: Chemical and physical processes driven by multiphoton absorption make possible the fabrication of complex, 3D structures with feature sizes as small as 100 nm. Since its inception less than a decade ago, the field of multiphoton fabrication has progressed rapidly, and multiphoton techniques are now being used to create functional microdevices. In this Review we discuss the techniques and materials used for multiphoton fabrication, the applications that have been demonstrated, as well as those being pursued. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
420
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(439 citation statements)
references
References 168 publications
2
420
0
9
Order By: Relevance
“…[4,5] A FA2F consiste em focalizar um feixe pulsado de femtossegundos no volume de uma resina polimérica contendo um fotoiniciador, composto orgânico responsável por desencadear a reação de polimerização quando excitado via absorção de dois fótons. [6] Diferente do que ocorre no processo de absorção linear, a taxa na qual a absorção de dois fótons ocorreé proporcionalà intensidade da radiação ao quadrado. Esta dependência não linear com a intensidade da radiaçãó e a característica responsável pelo confinamento espacial da excitação, que confereà técnica resolução abaixo do limite de difração.…”
Section: Aplicaçãounclassified
“…[4,5] A FA2F consiste em focalizar um feixe pulsado de femtossegundos no volume de uma resina polimérica contendo um fotoiniciador, composto orgânico responsável por desencadear a reação de polimerização quando excitado via absorção de dois fótons. [6] Diferente do que ocorre no processo de absorção linear, a taxa na qual a absorção de dois fótons ocorreé proporcionalà intensidade da radiação ao quadrado. Esta dependência não linear com a intensidade da radiaçãó e a característica responsável pelo confinamento espacial da excitação, que confereà técnica resolução abaixo do limite de difração.…”
Section: Aplicaçãounclassified
“…High resolution SEMs (Figure 2) show that the metallic patterns are comprised of small metallic granules, indicating that the rate of photoreduction within the focal volume is limited by the diffusion of metallic precursors. [32][33][34] SEM cross-sectional analysis of an exemplary Pd structure revealed that the granular surface, in large part, is continuous throughout the structure interior down to the glass/metal interface at which point the structure appears solidified, indicating thermal melting/annealing at the interface-a consequence of heating via light absorption by the metallic pads. We estimated the steady state temperature rise (ΔΤ) at the laser focal point of the glass/metal interface using the solution for the low frequency limit (essentially CW) of the laser modulation: 35…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Additionally MPL-Pt and Pd materials display excellent electronic and catalytic functionality; further enhancement is expected by exploring alloyed systems and controlling resolution and particle morphology using structure-directing agents ,1,32,43,44 or electroplating techniques. 34 Fabrication of Pt and Pd structures with free-form, 3D architectures is currently being investigated through judicial variation of the chemical and environmental parameters in an effort to overcome the low structure fidelity incurred via laser heating. 18,19,32 The ability to prototype arbitrary 3D microscale electroactive and catalytic surfaces provides a new toolset with which to fabricate dynamic, 3D nano/microscale systems.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Two-photon polymerization of monomer or prepolymer resins offers full 3D design flexibility at the sub-micron to millimeter length scales (LaFratta et al 2007). The upper limit of millimeters is effectively given by the low writing speeds achievable using the combination of currently available instrumentation, resins, and photoinitators.…”
Section: Introductionmentioning
confidence: 99%